Making ancient cities : space and place in early urban societies - Creekmore, Andrew T.; Creekmore, Andrew T.; Fisher, Kevin D.; Fisher, Kevin D. (Cambridge University Press, 2014)
This volume investigates how the structure and use of space developed and changed in cities, and examines the role of different societal groups in shaping urbanism. Culturally and chronologically diverse case studies provide a basis to examine recent theoretical and methodological shifts in the archaeology of ancient cities. The book's primary goal is to examine how ancient cities were made by the people who lived in them. The authors argue that there is a mutually constituting relationship between urban form and the actions and interactions of a plurality of individuals, groups, and institutions, each with their own motivations and identities. Space is therefore socially produced as these agents operate in multiple spheres